EVALUASI PENERAPAN UNDIKNAS MOBILE: ANALISIS TECHNOLOGY ACCEPTANCE MODEL - Krisnawijaya, Ngakan Kutha; Pradnya Dewi, I Gusti Ayu Agung (LPPM STMIK STIKOM Indonesia, 2019)
Undiknas Mobile is an application to facilitate students in carrying out their education. Based on the Technology Acceptance Model (TAM) with the addition of output quality and social influences this study aims to analyze the application of Undiknas Mobile through user intentions to continue using this system until they graduate from Undiknas University. This study is conducted by carrying a survey of 263 students at Undiknas university and use statistic descriptive as a technique of data analysis. The result of this study is the students have an intention to continue using Undiknas Mobile until they complete their study since they perceived the use and the ease of use of Undiknas Mobile. The output quality that is produced by Undiknas Mobile also accurate. In terms of social influences, it can be seen that only injunctive norm that can influence the users? intention to use Undiknas Mobile.